2019
DOI: 10.1097/won.0000000000000544
|View full text |Cite
|
Sign up to set email alerts
|

Development and Comparison of Predictive Models for Pressure Injuries in Surgical Patients

Abstract: PURPOSE: The purpose of this study was to develop and compare 3 predictive models for pressure injury (PI) occurrence in surgical patients. DESIGN: Retrospective case-control study. SUBJECTS AND SETTING: Data on PI risk assessment and preanesthesia evaluation records from 400 patients (80 patients who developed PIs after surgery and 320 patients who did not) in a South Korean acute care setting who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…The specific factors that were found to be significant were the estimated surgery time and serum albumin level. 72 Brain disease, which was not found to be significant in the "lean" Scott-Triggers model, emerged as significant in the extended version. Another recent risk assessment tool that has demonstrated effectiveness in identifying patients who are at risk of intraoperative PUs is called the "perioperative risk assessment measure for skin" (PRAMS 74 ;).…”
Section: Risk Assessment Tools For Surgical Patients and Relevance mentioning
confidence: 85%
See 3 more Smart Citations
“…The specific factors that were found to be significant were the estimated surgery time and serum albumin level. 72 Brain disease, which was not found to be significant in the "lean" Scott-Triggers model, emerged as significant in the extended version. Another recent risk assessment tool that has demonstrated effectiveness in identifying patients who are at risk of intraoperative PUs is called the "perioperative risk assessment measure for skin" (PRAMS 74 ;).…”
Section: Risk Assessment Tools For Surgical Patients and Relevance mentioning
confidence: 85%
“…Their logistic regression model to identify significant factors showed, as expected, that, while the Braden tool cannot identify any significant factor that predicts intraoperative PUs, the Scott‐Triggers tool (with or without the additional items) does have a predictive value. The specific factors that were found to be significant were the estimated surgery time and serum albumin level 72 . Brain disease, which was not found to be significant in the “lean” Scott‐Triggers model, emerged as significant in the extended version.…”
Section: Prevalence and Risk Factors For Intraoperatively Acquired Timentioning
confidence: 93%
See 2 more Smart Citations
“…Potential validated instruments include the Braden Scale for Pressure Sore Risk (Braden Scale), Munro Scale, Scott Triggers, and the Perioperative Risk Assessment Measure for Skin (PRAMS) Scale. 14 The Braden Scale was not developed for evaluation of risk during surgical procedures and has a low predictive validity for this population. 15 However, Meehan and colleagues 16 found that a Braden Scale score of less than 16 emerged as an independent risk factor for PI development-based multiple logistic regression analysis.…”
Section: Risk Assessmentmentioning
confidence: 99%